PEMBERIAN ASI EKSKLUSIF TERHADAP KEJADIAN ISPA PADA BAYI USIA 6-12 BULAN - Ikasari, Filia Sofiani; Pertiwiwati, Endang; Rachmawati, Kurnia (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2015)
Acute respiratory tract infection (ARI) is one of health problem in the world including in Indonesia.Many factors contribute to the high incidence of ARI, one of many factors is the duration ofbreastfeeding. Breast milk contains antibodies that protected babies from diseases. This study aimsdetermined there was a relationship between exclusive breastfeeding and ARI among infants aged 6-12 months in Puskesmas Martapura’s working area. This research was quantitative researched withcase control design. The sample used simple random sampling in 77 cases and 77 control groupinfants aged 6-12 months. Case group were infants aged 6-12 months with ARI and control groupwere infants aged 6-12 months that didn’t experience ARI. Furthermore, researcher identificatedexclusive breasfeeding at respondents retrospectively. The result showed that infants who didn’texclusively breastfed have odd ratio 0.454 times (95% CI: 0.238 to 0.865) for experienced ARI thanexclusively breastfed infants, with a value of p=0.024. based on the results, it concluded that therewas a relationship between exclusive breastfeeding and ARI among infants aged 6-12 months inPuskesmas Martapura’s working area. This research useful to be reference to next research about theimportance of exclusive breastfeeding promotion to prevent ARI in infants.